Resolution-Based Therapies: The Potential of Lipoxins to Treat Human Diseases - Jaén, Rafael I.; Sánchez-García, Sergio; Fernández-Velasco, María; Boscá, Lisardo; Prieto, Patricia (Frontiers in Immunology, 2021)
Inflammation is an essential response of the organism to injury and its adequate resolution is essential to restore homeostasis. However, defective resolution can be the precursor of severe forms of chronic inflammation and fibrosis. Nowadays, it is known that an excessive inflammatory response underlies the most prevalent human pathologies worldwide. Therefore, great biomedical research efforts have been driven toward discovering new strategies to promote the resolution of inflammation with fewer side-effects and more specificity than the available anti-inflammatory treatments. In this line, the use of endogenous specialized pro-resolving mediators (SPMs) has gained a prominent interest. Among the different SPMs described, lipoxins stand out as one of the most studied and their deficiency has been widely associated with a wide range of pathologies. In this review, we examined the current knowledge on the therapeutic potential of lipoxins to treat diseases characterized by a severe inflammatory background affecting main physiological systems, paying special attention to the signaling pathways involved. Altogether, we provide an updated overview of the evidence suggesting that increasing endogenously generated lipoxins may emerge as a new therapeutic approach to prevent and treat many of the most prevalent diseases underpinned by an increased inflammatory response.